National Pediatric Hematopoietic Stem Cell Transplantation Activity in Turkey - Kansoy, S.; Hazar, V.; Kupesiz, A.; Uckan, D.; Kuskonmaz, B.; Tezcan, I.; Aksoylar, S.; Tezcan, G.; Kilic, S. Caki; Ertem, M.; Unal, E.; Ikinciogullari, A.; et al. (NATURE PUBLISHING GROUP, 2015)
41st Annual Meeting of the European-Society-for-Blood-and-Marrow-Transplantation, Istanbul, TURKEY, MAR 22-25, 2015